(untitled) (Medical Forum Monthly, 2020)
Objective: To evaluate the left-ventricular size in early postoperative periodin patients with aortic regurgitation after aortic valve replacement. Study Design: Retrospective Observational study. Place and Duration of Study: This study was conducted at the Multan Institute of Cardiology from January 2012 and January 2020. Materials and Methods: Data was collected from 116 patients with severe chronic aortic regurgitation, who underwent AVR in which transthoracic echocardiograms was performed before and after the surgery. The left ventricular calculations such as LVEDD, LVESD, posterior wall thickness (PWT), and interventricular septum (IVS) were collected as per recommended standards. In our study ≥10% reduction in left ventricular volumes [4] is referred to as reverse left ventricular remodeling as measured by either Teichholz or modified Simpson’s methods. Mean ± standard deviation was used for summarizing continuous variables and were compared using t test while Fisher’s exact test was used to summarize as count and to compare the categorical variables. The difference between ∆LVESViTeichnolz and ∆LVESViSimpson, and ∆LVEDViTeichnolz and ∆LVEDViSimpson were calculated by estimation of spearman correlations and 95% confidence intervals. Moreover, the assessment of positive and negative agreement by LVEDV and LVESV measurements were done by cross-tabulation of diameter and volume-based left ventricular remodeling individually. Results: The mean Interventricular septum thickness, left ventricular end-diastolic diameter, indexed left ventricular end-diastolic diameter, left ventricular end-systolic diameter, indexed left ventricular end-systolic diameter, posterior wall thickness, indexed left ventricular mass, left ventricular outflow tract diameter, aortic root diameter and ascending aorta diameter of the patients pre-AVR, was 1.17±0.83, 6.51±1.18, 3.68±1.26, 4.21±1.38, 2.37±1.49, 1.22±0.27, 134.5±13.13, 2.41±1.43, 4.61±0.61, and 4.62±1.25 respectively. The mean Interventricular septum thickness, left ventricular end-diastolic diameter, indexed left ventricular end-diastolic diameter, left ventricular end-systolic diameter, indexed left ventricular end-systolic diameter, posterior wall thickness, indexed left ventricular mass, left ventricular outflow tract diameter, aortic root diameter and ascending aorta diameter of the patients post-AVR was, 1.27±0.29, 5.16±0.51, 2.64±0.47, 3.49±0.94, 2.03±0.48, 0.99±0.09, 115.41±11.12, 2.01±0.11, 3.17±0.31, and 3.03±0.32 respectively. Conclusion: The outcomes of our study proposed that left ventricular volumes were better than left ventricular diameter measurements for assessment of the reverse remodeling. On the other hand, large scale studies must be conducted in order to conclude whether volumes of the left ventricular also influence outcomes in the long-term.